Exposure to diverse political views in contemporary media environments - Steinfeld, Nili; Lev-on, Azi (Frontiers in Communication, 2024)
Exploring the nexus between digital media and citizens' exposure to diverse political views is imperative for understanding contemporary democratic engagement. This study builds upon Mutz and Martin's (2001) seminal research, integrating digital communication channels previously unexamined. Our findings suggest that the interpersonal character of media interactions, rather than the mere distinction between offline and online platforms, significantly influences the diversity of political views to which individuals are exposed. Contrary to the prevalent theories of 'echo chambers' and 'filter bubbles,' our analysis reveals a nuanced media landscape where digital platforms facilitate both homogeneous and heterogeneous political exposures, depending on their specific affordances. This study contributes to the political communication literature by offering a comprehensive overview of exposure dynamics in the digital age.